Between Mining and Justice: Reconstructing Responsible Mining in the Framework of Indonesian Mining Law - Sinung Mufti Hangabei; Hendi Sastra Putra; Mikho Ardinata; Edi Riyanto (Universitas Muhammadiyah Tangerang, 2023)
Mining governance in Indonesia often shows a gap between the constitutional mandate of natural resource management under Article 33 of the 1945 Constitution and its practical implementation, particularly in relation to social justice, environmental sustainability, and the welfare of local communities. This study aims to analyze the concept of responsible mining within Indonesian mining law and to reconstruct its legal foundation based on the principles of social justice and constitutional resource governance. This research employs normative legal research using statutory and conceptual approaches. Legal materials are analyzed qualitatively to examine the relationship between constitutional principles, mining regulations, and the concept of responsible mining. The study reveals that Indonesian mining law still demonstrates a misalignment between constitutional mandates and mining practices, limited integration of social justice, weak legal orientation toward local community welfare, and normative ambiguity in the concept of responsible mining. This research proposes the reconstruction of responsible mining as a constitutional legal principle grounded in Article 33 of the 1945 Constitution and strengthened through the integration of the social licence to operate concept in mining governance.